Selection of surgical treatment tactics of critical CoA with concomitant intracardiac defects in newborns - Lekan, R. I.; Buzovsky, V. P.; Lekan, I. R. (Ukrainian Journal of Cardiovascular Surgery, 2018)
CoA in infants as an isolated anomaly occurs in 50% of cases. ASD occurs in 20% among the concomitant anomalies and the remaining 30% occupy other anomalies. One of the approaches is total surgical repair fully correct anomalies due to median sternotomy with cario-pulmonary bypass, deep hypothermia and antegrade cerebral perfusion. As an alternative is an approach with left-side thoracotomy and PA banding, in the presence of septal defects or a single ventricle with pulmonary hypertention. The purpose of this work is the choice of tactics of surgical treatment of critical CoA with hypoplasia of the distal aortic arch and associated intracardiac septal defects in newborns. Matherials and methods. 33 newborns with a critical CoA and hypoplasia of DSA were operated in the Department of cardiosurgery Odessa Children Hospital From 2007 to 2017, 13 of them had significant intracardiac anomalies. Newborns were performed laboratory and instrumental research methods, Z-score arithmetic of the aortic segments were calculated for determination of indications for surgical correction. The operation was performed through the left posterolateral thoracotomy in the 4 intercostal areas. All stages were completed within one operation. 13 (39,4%) infants with CoA and hypoplasia of DDA and septal defects and PH were performed PA banding first of all and the next stage was the procedure Amato and EAEtoE. 32 patients undergone surgery well, but 1 died (3.0%) in the early postoperative period from bleeding from tracheobronchial tree. Plastic of DDA in the modification of Amato ensured a significant increase in the lumen of the aorta immediately after surgery, according to Echo. In the remote period, on average, after 4.7 years, a significant increase in arc segments and aneurysm aorta was observed. The primary operation of PA banding with significant septal defects stabilizes hemodynaics and creates conditions for safe plastic DDA and EAEtoE, and the effectiveness of modification of the operation Amato is suspended in the distant period in 93.7% of the patients with CoA correction with the expressed dysplasia DDA.